Methods Of Evaluating Adaptation And Accuracy Of Additive Manufactured Removable Partial Dentures: A Scoping Review - Safa Elhadery; Syarida Hasnur Safii; Norliza Ibrahim; Zubaidah Zainul Abidin; Nosizana Mohd Salleh; Norlela Yacob (Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus/ERA/MyCite